The Relationship Between Parenting and Nutrition-Aware Family Behavior with The Incidence of Stunting in Toddlers at Klaten Regency Central Java Province - Linda Rosalina; Brivian Florentis Yustanta; Novia Wahyu Wardani; Devin Mahendika; Ponco Indah Arista Sari; Tanwir Djafar (Jurnal Penelitian Pendidikan IPA, 2023)
The Nutrition Awareness Family (Kadarzi) is an Indonesian government program that aims to address the problem of malnutrition. The indicators for assessing KADARZI status are weighing, eating a variety of foods, breastfeeding, use iodized salt, consume vitamin A. Babies are weighed every month to monitor their growth and development. Infants aged 1 to 5 years are weighed every month at the Posyandu. This study aims to determine the relationship between the application of the Kadarzi behavior and the incidence of stunting in toddlers aged 24-59 months. This correlative study used a cross sectional design . Research that focuses on measuring and collecting data at one time is done by correlating the independent variables and the dependent variable. Family that has implement KADARZI and have fulfil whole specified indicator _ with Good as many as 28 families with percentage 56%. 22 families Not yet apply the KADARZI program with percentage 44%. Conclusions obtained from study This is there is connection between implementing family _ behavior KADARZI with incident stunting in the district Klaten Province Central Java shown from p-value 0.011.